Developmental Theories: The Role of Genetic and Environmental Influences in Childhood, Classic and Modern Developmental Theories - Mirić, Jovan (Social and Personality Development in Childhood, 2025)
This text begins with an outline of the nature-nurture debate. Next, it introduces the six key theories of developmental psychology: Freud, Erikson, Piaget, Vygotsky, and Bowlby, and the social learning theory (SLT). Some of the theories presented focus on personality as a whole, while others refer mainly to cognitive development, socialisation, etc. Some take firm positions on stages (Piaget, Freud, and Erikson), others do not (Vygotsky and Bowlby), and some do not even include stages in their conceptual corpus (SLT). Erikson’s theory covers the entire life course, while other theories cover stages up to maturity. Sources of the individual theories are indicated: clinical work for the theories of Freud and Erikson, the epistemological problem for Piaget’s theory, Marxism for Vygotsky’s theory, and a combination of two traditions (stimulus-response learning theory and psychoanalysis) for SLT. The general propositions of the key theories are presented, followed by specific issues of psychological development. The text comments on each theory’s developmental factors: biological, environmental (physical, social, cultural), and individual activity. An outline of two further orientations in developmental psychology is provided at the end. Keywords: factors of development, stages of development, learning and maturation, attachment, imitation